Associação entre excesso de peso e qualidade de vida em adolescentes : uma revisão sistemática - Souza, Micheline Lopes de Albuquerque (2012)
Studies show that early obesity leads to an increased risk of obesity in adulthood. Overweight (overweight and/or obesity) can affect the quality of life in adolescents whose improvement is probably the most desirable outcome of all health policies. Objective - To assess scientific evidence of association between overweight and health related quality of life in adolescents. Methods - Systematic review of six electronic databases; without the restriction of dates, languages, periodicals or outlining of the studies. Primary studies showing an association between overweight and quality of life in adolescents, were included. We excluded studies on samples of pregnant adolescents or obesity adolescents with associated pathologies. An evaluation of agreement was assessed between reviewers at all stages and the methodological quality of selected articles was assessed. Results - 17 articles were identified with great heterogeneity in the instruments of quality of life, weight classification and forms of analysis of the association. Still, it is noticed that obese adolescents have a worse quality of life than the overweight and eutrophic ones, impacting more on the physical domain. Conclusion – The qualitative analysis showed that there is an association between overweight and quality of life in adolescents. As the parameters of weight increase, the quality of life decreases. The quantitative analysis through meta-analysis may confirm the strength of the evidence found. Obese adolescents show lower scores of quality of life than overweight ones. There was more evidence of the impact of overweight in the physical domain of quality of life.